Librarians and Marketing: An Ambiguous Relationship - Neslihan Uraz (Türk Kütüphaneciliği)
While librarians show a growing interest for marketing, their concept of marketing seems inaccurate. Librarians' outlook is mostly organizational, and focused on sales- and product-oriented stratégies which fail to embrace a truly client-centered marketing orientation. After a brief review of the literature, the author reports on a qualitative study confirming that the marketing orientation, as defined by experts, is insufficiently developed among librarians.